PERBEDAAAN KEMAMPUAN PEMECAHAN MASALAH DAN BERPIKIR KREATIF MATEMATIKA SISWA YANG DIAJARKAN DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DAN PEMBELAJARAN KOOPERATIF TIPE TWO STAY-TWO STRAY PADA MATERI SISTEM PERSAMAAN LINEAR TIGA VARIABEL KELAS X SMA - Rani Endriani; Fibri Rakhmawati (AXIOM : Jurnal Pendidikan dan Matematika, 2019)
This study aims to determine whether there are differences in the ability to solve problems and think creatively in mathematics students who are taught with the problem based learning model with the two-stay-two stray cooperative learning model in class X SMA Negeri 2 Range of TP 2018 / 2019. This research is research quantitative research with quasi-experimental type. This sampling technique uses the Cluster Random Sampling technique. The sample of this study was students of class X-1 and X-2 of SMA Negeri 2 Kisaran T.P 2018/2019, amounting to 60 students. The test instrument used to determine students' creative problem solving abilities and mathematical creative thinking is to use a test in the form of a description. Data analysis was performed by analysis of variance (ANAVA). These findings show: 1). There is a difference in the ability to solve mathematical problem of students who are taught with the Problem Based Learning model and the Two Stay-Two Stray cooperative learning model in the material of the Three Variable Linear Equation System; 2). There is no difference between students' creative thinking abilities in mathematics taught by the Problem Based Learning model and the Two Stay-Two Stray cooperative learning model in the Three Variable Linear Equation System material; 3). There is a difference in the ability of problem solving and mathematical creative thinking of students who are taught with the Problem Based Learning model and the Two Stay-Two Stray cooperative learning model in the material of the Three Variable Linear Equation System; 4). There is no significant interaction between the learning models used on the problem solving abilities and students' mathematical creative thinking in the Three Variable Linear Equation System material. The conclusions in this study explain that there are differences in students' problem solving abilities and creative mathematical thinking that are taught with the Problem Based Learning Model and the Two Stay-Two Stray Cooperative Learning Model.